Temporal shifts in intraguild predation pressure between beluga whales and Greenland halibut in a changing Arctic. (8th November 2017) - Yurkowski, David J.; Hussey, Nigel E.; Fisk, Aaron T.; Imrie, Kendra L.; Tallman, Ross F.; Ferguson, Steven H.
Abstract : Asymmetrical intraguild predation (AIGP), which combines both predation and competition between predator species, is pervasive in nature with relative strengths varying by prey availability. But with species redistributions associated with climate change, the response by endemic predators within an AIGP context to changing biotic–abiotic conditions over time (i.e. seasonal and decadal) has yet to be quantified. Furthermore, little is known on AIGP dynamics in ecosystems undergoing rapid directional change such as the Arctic. Here, we investigate the flexibility of AIGP among two predators in the same trophic guild: beluga ( Delphinapterus leucas ) and Greenland halibut ( Reinhardtius hippoglossoides ), by season and over 30 years in Cumberland Sound—a system where forage fish capelin ( Mallotus villosus ) have recently become more available. Using stable isotopes, we illustrate different predator responses to temporal shifts in forage fish availability. On a seasonal cycle, beluga consumed less Greenland halibut and increased consumption of forage fish during summer, contrasting a constant consumption rate of forage fish by Greenland halibut year-round leading to decreased AIGP pressure between predators. Over a decadal scale (1982–2012), annual consumption of forage fish by beluga increased with a concomitant decline in the consumption of Greenland halibut, thereby indicating decreased AIGP pressure between predators in concordance with increased forage fish availability. The long-term changes of AIGP pressure between endemic predators illustrated here highlights climate-driven environmental alterations to interspecific intraguild interactions in the Arctic.